Dicer and R2D2 - Lee, Young Sik (Henry Stewart Talks, 2007)
Double-stranded RNA (dsRNA) processing by Dicer, dsRNA-binding domain (dsRBD) protein partners (e.g. R2D2) of Dicer, Dicer-mediated RISC assembly, Sensing of thermodynamic asymmetry of small RNA duplexes by the Dicer/dsRBD partner complex
Reviewed at 2015/08/21